A Rare Case of Metastasis of Renal Clear Cell Carcinoma to the Thyroid Gland, Presenting as a Goiter Nodule, Three Years After Nephrectomy - Hedieh Moradi Tabriz; Arezoo Eftekhar-Javadi; Atiieh Zandnejadi (Iranian Society of Pathology, 2020)
Thyroid gland metastatic tumors are rare in clinical practice. Clear cell RCC is one of common metastatic tumors to thyroid. We here reported a case of incidentally found clear cell renal carcinoma metastasis to the thyroid gland 3 years after nephrectomy, in the thyroidectomy procedure performed for the patient due to the thyroid enlargement caused by multinodular goiter. A 65-year-old Iranian man with a history of multinodular goiter referred to our surgery clinic for thyroidectomy because of compressive effects on the trachea. Patient had a history of nephrectomy due to clear cell RCC 3 years ago. After thyroidectomy, gross and histological examination of thyroid revealed clear cell renal carcinoma metastasis to the thyroid gland in the setting of a multinodular goiter. The diagnosis was confirmed by immunohistochemistry staining. Patients with multinodular goiter are more prone to present with metastasis to thyroid gland if they have a history of malignancy, especially renal cell carcinoma.